Calculation of unbalanced magnetic pull in induction machines through empirical method. Issue 9 (8th June 2018) - Chuan, Hawwooi; Shek, Jonathan K.H.
Abstract : Unbalanced magnetic pull (UMP) occurred due to the uneven distribution of magnetic flux around the airgap, which can be caused by the existence of rotor eccentricity in the machines. Here, a UMP damping coefficient is introduced to explain the UMP damping effect from the counteracting flux produced by a parallel‐connected cage rotor. An empirical method is proposed to calculate the UMP using the damping coefficient and an analytical model. Using the proposed method, a four‐pole and eight‐pole squirrel cage induction machine with static eccentricity are investigated, which uses inputs from both finite element analysis and experimental work. Then, the UMP calculation for a dynamic eccentricity with the extracted parameters is done to verify the empirical method. A slip control method is described which uses a UMP/torque ratio to find the operating slip with the lowest UMP. Comparisons between results with and without slip control are made on both induction machines. It shows that great reduction in UMP can be achieved when the machine is lightly loaded.